What a drag it is being relational: Developing planetary identities. Issue 4 (29th September 2020) - Bauman, Whitney A.
Abstract: Feminists scholars, among others, have long argued for a relational understanding of identity and the self. More recently queer theory and the new materialisms have taken that understanding and placed it within an evolutionary and planetary perspective. As most modern, western understandings of law, politics, and ethics take the individual as the base unit for reflection, what might this relational, planetary identity mean in terms of ethics? This brief essay explores some of the religious and theoretical supports for a relational, planetary self, and then develops a type of ethic that is based upon a critical romanticism for the planet.